Proposta para regulação da eficiência energética nos sistemas elétricos de consumidores - Ortega, Bernardo Gustavo Páez (2006)
This dissertation develops for the improvement of the energy efficiency of the electric systems with the proposal of elaborating efficient electric projects for consumers in buildings of collective use and in industries. For this search they are elaborated case studies that show the viability of this improvement with alterations of norms and existent patterns, which lead to the suggestion of if they elaborate of studies of adaptation of the current regulation seeking to the economy of energy starting from the careful and discerning preparation of the electrical installations project.